(untitled) (Olhar de Professor, 2020)
The article presents the analyzes of publications that report empirical researches of three Brazilian groups that are references for Special Inclusive Education: the Laboratory of Studies on Prejudice, the National Observatory of Special Education and the Laboratory of Studies and Research in Teaching and Difference. The theoretical-methodological course included bibliographic documentary research for the selection of articles and the analyzes are based on the Critical Theory of Society and on authors from the thematic content of Special Inclusive Education. The results indicate two inseparable categories, the first concerns the prejudice that runs through the relationships between children, but also between teachers and students. The second refers to the feeling of insecurity and unpreparedness of teachers to formulate special activities and promote the inclusion of students with special needs.